An Experimental Study on the Attribution of Personality Traits to Bullies and Targets in a Workplace Setting - Pallesen, Ståle; Nielsen, Morten B.; Magerøy, Nils; Andreassen, Cecilie S.; Einarsen, Ståle (Frontiers in Psychology, 2017)
Previous studies on the personality of bullies and targets have exclusively been based on self-report. Against this backdrop we conducted a between group experimental vignette study with three conditions, describing a bully, a target and a control, respectively. Students (n=242) were recruited as participants and rated the target on the observer rating version of the NEO Five Factor Inventory-Revised reflecting the personality dimensions Neuroticism, Extroversion, Openness to experience, Agreeableness and Conscientiousness. A MANOVA showed an overall significant effect of the experimental conditions. On Neuroticism significant differences between all conditions were found with targets rated highest and the control lowest. In terms of Extroversion the target was rated as lower than the control and the bully. No main effect was found for Openness. On Agreeableness the bully was rated as lower than both the target and the control. The bully was rated lower on Conscientiousness than the control. The significant differences reflected medium to large effect sizes. By and large the results are in agreement with comparable self-report data. The results are discussed in terms of practical implications and directions for future research are outlined.